The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1136/bmjopen-2013-003663
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-induced cardiotoxicity: prospective cohort study from Pakistan

Abstract: ObjectivesTo identify anthracycline-induced acute (within 1 month) and early-onset chronic progressive (within 1 year) cardiotoxicity in children younger than 16 years of age with childhood malignancies at a tertiary care centre of Pakistan.DesignProspective cohort study.SettingAga Khan University, Karachi, Pakistan.Participants110 children (aged 1 month–16 years).InterventionAnthracycline (doxorubicin and/or daunorubicin).Outcome measurementsAll children who received anthracycline as chemotherapy and three ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
5
9
2
2
Order By: Relevance
“…PCs 1–10 did not significantly differ between cases and controls ( P >0.14) and the λ GC of 0.941 suggested no confounding effect of population stratification on the genetic association of rs2229774 with ACT in this cohort. In line with the reported high incidence of ACT in studies conducted in India 30 and Pakistan 31 , and in African-American patients in the USA 23 , 24 , RARG rs2229774 is more frequent in South Asian (22%) and African populations (11%) compared to European (6%) and Hispanic (5%) populations. By contrast, rs2229774 is very rare in East Asian (0%) populations (1000 Genomes).…”
Section: Introductorysupporting
confidence: 65%
“…PCs 1–10 did not significantly differ between cases and controls ( P >0.14) and the λ GC of 0.941 suggested no confounding effect of population stratification on the genetic association of rs2229774 with ACT in this cohort. In line with the reported high incidence of ACT in studies conducted in India 30 and Pakistan 31 , and in African-American patients in the USA 23 , 24 , RARG rs2229774 is more frequent in South Asian (22%) and African populations (11%) compared to European (6%) and Hispanic (5%) populations. By contrast, rs2229774 is very rare in East Asian (0%) populations (1000 Genomes).…”
Section: Introductorysupporting
confidence: 65%
“…This would suggest that altered extracellular matrix within the heart should also be altered leading to compromised function and such an outcome might be reflected as altered diastolic dysfunction. Several cohort studies have reported diastolic and diastolic plus systolic dysfunction as an outcome of doxorubicin treatments in different patient population including children [16] , [81] , [111] . Ivanová et al and others have demonstrated that mRNA and protein levels of several matrix metalloproteinases were significantly increased in cardiomyocytes by doxorubicin [3] , [38] .…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…8 Penelitian lain yang mengidentifikasi efek kardiotoksik obat golongan antrasiklin yang digunakan dalam terapi keganasan pada anak di Pakistan menemukan bahwa 14% anak mengalami disfungsi jantung dalam satu bulan paska terapi antrasiklin. 9 Efek kardiotoksik antrasiklin secara klinis memberikan gambaran klinis gagal jantung, sementara secara subklinis hanya memberikan gambaran kelainan jantung melalui berbagai metode diagnostik tapi secara klinis asimptomatik. 7 Efek kardiotoksik antrasiklin dapat bersifat akut (terjadi pada saat atau segera sesudah administrasi), yaitu dapat berupa perubahan pada gambaran elektrokardiografi (EKG) termasuk pemanjangan interval QT dan aritmia; subakut (dalam beberapa hari atau minggu setelah administrasi), termasuk miokarditis toksik atau perikarditis, dan dapat bersifat kronik (dalam beberapa minggu atau bulan setelah administrasi) yang bermanifestasi sebagai kardiomiopati.…”
Section: Hubungan Dosis Kumulatif Doksorubisin Terhadap Fungsi Sistolunclassified
“…Penelitian ini menemukan bahwa 14% pasien mengalami gangguan jantung berupa penurunan myocardial performance index melalui pemeriksaan ekokardiografi dalam waktu sebulan setelah selesainya terapi, yang meningkat menjadi 25% dalam satu tahun setelah selesainya terapi. 9 Hasil korelasi negatif yang bermakna antara dosis kumulatif doksorubisin dan fungsi sistolik ventrikel kiri yang ditemukan dari penelitian kami sejalan dengan hasil penelitian Lipshultz dkk, 15 yang melaporkan adanya hubungan yang bermakna antara penurunan fungsi jantung (meliputi kontraktilitas ventrikel kiri (stress-velocity index), dimensi ventrikel kiri di akhir fase diastol, massa ventrikel kiri, FP ventrikel kiri, afterload ventrikel kiri dan rasio ketebalan dinding terhadap dimensi ventrikel kiri) dengan dosis kumulatif doksorubisin yang lebih besar. Pada penelitian tersebut besaran korelasi tidak dinilai, melainkan digambarkan dalam bentuk kurva z-score.…”
Section: Pembahasanunclassified